Prevalence of anti-toxoplasma antibodies in patients with autoimmune diseases (2012)
The identification of etiological factors in the induction of autoimmunity has remained elusive despite an enormous effort at dissection of the molecular structure of the target antigens and effector mechanisms. One characteristic feature of autoantigens is their repetitive structure as well as their conservation and evolution. Toxoplasma (T.) gondii is a primitive protozoan. We hypothesized that patients with autoimmune disease would have broad reactions against Toxoplasma antigens based on autoantigen conservation. To address this issue, we assessed serologic evidence of reactivity to Toxoplasma gondii along with a large profile of autoantibodies in patients with various autoimmune diseases (AID). We included sera of 1514 patients with 11 different AID collected from referral centers in Europe and Latin America as well as from 437 geographically matched controls, for the prevalence of anti Toxoplasma antibodies (ATxA) IgG and IgM and serum autoantibodies utilizing the BioPlex 2200 system (Bio- Rad Laboratories, USA). Serum ATxA IgG were positive in 42% of patients with AID versus 29% of controls (p < 0.0001). Among Europeans, ATxA IgG were associated with anti-phospholipid syndrome (APS; p < 0.0001), cryoglobulinemia (p < 0.0001), ANCA-associated vasculitides (p < 0.01), autoimmune thyroid diseases (p < 0.0001), systemic sclerosis (SSc; p < 0.0001) and rheumatoid arthritis (RA; p < 0.0001). Of note, Latin American RA sera exhibited similar frequency of ATxA IgG as controls. ATxA IgM were more prevalent in European patients with APS (p < 0.01), SSc (p < 0.05) and inflammatory bowel disease (IBD, p < 0.05) than in controls. Further, in AID patients the presence of ATxA correlated with autoantibodies characteristic of APS (anti- cardiolipin, B2GPI, complex of cardiolipin- B2GPI, prothrombin, phosphatydilethanolamine), and of SSc (anti-centromere, Scl-70). Our findings suggest that T. gondii may contribute to the pathogenesis of AID. This interaction may depend on or explain observed geoepidemiological variance in AID.